2016
DOI: 10.1016/j.mvr.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT angiography detects vascular formation and regression in skin wound healing

Abstract: Properly regulated angiogenesis and arteriogenesis are essential for effective wound healing. Tissue injury induces robust new vessel formation and subsequent vessel maturation, which involves vessel regression and remodeling. Although formation of functional vasculature is essential for healing, alterations in vascular structure over the time course of skin wound healing are not well understood. Here, using high-resolution ex vivo X-ray micro-computed tomography (microCT), we describe the vascular network dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
(29 reference statements)
2
21
0
Order By: Relevance
“…Wound blood vessels subsequently increase in number and branch pattern until they peak at 7 DPI, after which they resolve away from the wound area, becoming more organised and beginning to return to a distribution and alignment pattern resembling unwounded skin by 14 DPI (Fig 1B-D). This time course of events complements and expands on previous studies examining sprouting and regression of wound blood vessels using completely different technologies such as MicroCT angiography imaging (Urao et al, 2016). ▸ Figure 1.…”
Section: Resultssupporting
confidence: 73%
“…Wound blood vessels subsequently increase in number and branch pattern until they peak at 7 DPI, after which they resolve away from the wound area, becoming more organised and beginning to return to a distribution and alignment pattern resembling unwounded skin by 14 DPI (Fig 1B-D). This time course of events complements and expands on previous studies examining sprouting and regression of wound blood vessels using completely different technologies such as MicroCT angiography imaging (Urao et al, 2016). ▸ Figure 1.…”
Section: Resultssupporting
confidence: 73%
“…A CD31 antibody has frequently been used to stain endothelial cells. 11,21,24,25 In this study, the results of paired measurements obtained from 2D ultrasound images with the Color Doppler mode and immunohistologically stained sections on day 14 after wounding showed that Pearson's correlation coefficients were r=0.927, 0.871, 0.717, and 0.913 for wounds 1, 2, 3, and 4, respectively, indicating a correlation. This result showed that a strong correlation for % vascularity was obtained between paired 2D ultrasound imaging with the Color Doppler mode and sections immunohistologically stained for the anti-CD31 antibody.…”
Section: Discussionmentioning
confidence: 53%
“…Other imaging modalities such as laser speckle perfusion imaging 22,23 and ex vivo micro CT imaging 11 have been used to visualize the vasculature of wounds or burns; however, there are some limitations. Laser speckle perfusion imaging is a non-invasive technique for Therefore, due to these limitations, high-resolution ultrasound imaging is considered a suitable modality for longitudinally monitoring the 3D structure of the vasculature in full-thickness cutaneous wounds over the course of healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations